Anaerobic treatment of oil-contaminated wastewater with methane production using anaerobic moving bed biofilm reactors. (15th October 2019) - Morgan-Sagastume, F.; Jacobsson, S.; Olsson, L.E.; Carlsson, M.; Gyllenhammar, M.; Sárvári Horváth, I.
Abstract: Oil-contaminated wastewaters are generally treated by a combination of physico-chemical and biological methods. Interest in the anaerobic treatment of oily wastewaters has increased since it complements aerobic treatment and produces energy in the form of methane. The objectives of this study were to characterise the anaerobic process spontaneously occurring in a full-scale storage tank at a facility treating waste oil and oil-contaminated effluents, and to evaluate the applicability of an anaerobic moving bed biofilm reactor (AnMBBR) and an anaerobic contact reactor (ACR) for treating the oil contaminated wastewater feeding the storage tank. Three lab-scale reactors were operated in parallel over 465 days: one mesophilic and one thermophilic AnMBBR, and one thermophilic ACR. The wastewater had a high strength with an average chemical oxygen demand (COD) of 36 g/L with a soluble fraction of 80%. The BOD7 /COD ratios varied between 0.1 and 0.5, indicating low aerobic degradability. However, biomethane potential tests indicated some level of anaerobic degradability with methane yields between 150 and 200 NmL/gCOD. The full-scale storage tank operated at low organic loading rates (0.35–0.43 kgCOD/m 3 d), and long hydraulic retention times (HRT = 83–104 d). In comparison, the AnMBBRs achieved similar COD reductions (60%) as the full-scale tank but at a much shorter HRT of 30 d. Similar efficiency could only be reached at longer HRTs (43 d) in the ACR due to low biomass levels resulting from poor sludge settleability. The methane yield was higher (210 NmLCH4 /COD removed) in the AnMBBR operated at 37 °C, compared to the other reactors working at 50 °C (180 NmLCH4 /COD removed). This reactor also maintained a higher COD removal (67%) at an increased OLR of 1.1 kgCOD/m 3 d than the AnMBBR at 50 °C. The microbial composition of the biomass from the full-scale tank and the laboratory reactors provided evidence for the conversion of oil-contaminated wastewater into methane with a relatively high abundance of hydrogenotrophic methanogens. Graphical abstract: Image 1 Highlights: Anaerobic treatment of oily wastewater was investigated in both full and lab scale. The AnMBBR was able to handle double to triple the OLR than the full-scale tank. AnMMBRs achieved similar COD reduction (60%) at much shorter HRT (30days). Mesophilic AnMBBR performed better with higher treatment capacity than thermophilic. AnMBBR has a potential to treat wastewaters with oil derivatives and toxic compounds.